Heterogeneity of Campylobacter jejuni and Campylobacter coli strains from healthy sheep - Acik, Mehmet Nuri; Cetinkaya, Burhan (Elsevier Science Bv, 2006)
The objectives of this study were to identify, at species level, thermophilic campylobacters isolated from clinically healthy sheep by a multiplex polymerase chain reaction (mPCR). The heterogeneity among Campylobacter jejuni and C coli isolates was also investigated using a restriction fragment length polymorphism (RFLP) analysis of the flagellin (flaA) gene. Samples of intestinal contents, gall bladders and faeces were collected from 610 healthy sheep. While gall bladder samples were plated directly onto Preston agar, an enrichment stage was applied for intestinal and faecal samples. Of the 610 samples, 302 (49.5%) were positive for Campylobacter spp. Using a mPCR assay for species identification, 103 (34.1%) were positive with C jejuni-specific primers, while 100 (33.1%) were positive with C. coli-specific primers. Additionally, 16 (11.9%) of the intestinal content samples were positive for both species by mPCR. All the isolates identified as C jejuni and C coli were successfully subtyped by flaA typing. Of 203 isolates tested, 48 different flaA types were found. Twenty-six flaA types were identified among C jejuni isolates and the remaining 22 from C coli isolates. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Campylobacter jejuni; Campylobacter coli; sheep; m-PCR; flaA gene; RFLP